The Image of Sultan Abdul Hamid II in the Arabic Sources (A Study of his Policy towards the Constitutional Issue and the Palestinian Issue, 1876-1909) - Saadeh, Alaa; Al-Tlohi, Mujahed Jamal (Jordan Journal for History and Archaeology, 2023)
This study sheds light on the position of the Arab sources on the policy of the Ottoman Sultan Abdul Hamid II regarding the constitutional issue and the Palestinian cause. Specific examples were selected from the Arabic sources that reflect different points of view on the positions of Sultan Abdul Hamid II, and the most important issues of his time, such as his positions on the constitutional issue and the Palestinian cause, and the most important challenges he faced. The study relied on the historical, descriptive, and analytical method based on collecting the historical scientific material from its original sources, and then analyzing and using it in the formulation of historical events, as well as documenting it in a systematic historical manner.